SEJARAH PERKEMBANGAN RASM UTSMANI - Dian Febrianingsih (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Rasmul Quran is one part of the Qu'ran disciplines in which there learn about the writing of manuscripts of the Qur'an is done in a special way, both in the writing-pronunciation pronunciation and letter forms are used. Rasmul Qur'an also known as Ottoman Rasm. Koran Ottoman writing is writing attributed to Uthman ra. (Khalifah to III). The term appears after the completion of the copy of the Koran made by a team formed by Ustman in 25H. By the Ulama way of writing is usually termed the